Degradation studies of a commercial radiation-resistant polypropylene sterilized by gamma and electron beam technology before and after subsequent accelerated aging cycles - Kremser, Thomas; Susoff, Markus; Roth, Stefan; Kaschta, Joachim; Schubert, Dirk W. (Journal of Applied Polymer Science, 2019)
Irradiation is one of the most widely used technologies for sterilization of medical products. Unfortunately, some polymers in the medical field are susceptible to high-energy radiation. In the case of polypropylene, this leads to yellowing and embrittlement due to degradation mechanisms. This study compares the impact of gamma and eBeam sterilizations at a dose of 45 kGy on a commercially available, radiation-resistant polypropylene in combination with accelerated aging studies. Mechanical behavior as well as yellowing, accompanied by structural investigations like molar mass characterization and crystallinity analysis, have been investigated. It is shown that eBeam has less damaging effects compared with gamma irradiation. This is shown by an initial drop in elongation at break by 46% for gamma irradiated samples in contrast to 24% decrease using eBeam irradiation. Also, an initial drop in molar mass by 43% was found for gamma irradiated samples and by 27% for eBeam. Change in color was observed by an initial increase in the yellowness index of 42% at samples after gamma irradiation, respectively, of 22% for eBeam irradiated samples. Interestingly, molar mass remained constant during aging, whereas yellowing and Embrittlement further change. Additionally, empirical equations were found, which describe the experimental data. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48436.
CRIS-Team Scopus Importer:2019-09-17
Keywords: accelerated aging; degradation; polypropylene; radiation sterilization